STUDENT ATTITUDES TO PHYSICS LESSONS: IN CASE INDONESIA - Astalini Astalini; Dwi Agus Kurniawan; Siti hadijah; Rahmat Perdana (LPPM Universitas Negeri Yogyakarta, 2019)
The purpose of this research is to know the attitude of students in Batanghari High School toward physics learning. The type of research used in quantitative research is survey research design. The study involved 926 students of Senior High School in Batanghari District. Data collected through interview and questionnaire as many as 54 statement and used Likert scale 5 points and interview as a contributor to the questionnaire. Data analysis used is descriptive statistical analysis. The results of the analysis obtained on the indicator of the normality of scientists are 50.6% of students categorized well. The attitude indicator in physics as much as 46% are categorized well. The indicator of enjoyment in learning physics of 55.5% is categorized as good enough attitude. then the indicator of career interest in the field of physics by 45% is categorized quite well. Based on these results in part at Batanghari Senior High School students have a poor attitude towards the learning of physics.